2010
DOI: 10.1177/1048371309359612
|View full text |Cite
|
Sign up to set email alerts
|

My Name Is Maria: Supporting English Language Learners in the Kindergarten General Music Classroom

Abstract: For many young children who are English language learners (ELLs), the transition from home to kindergarten can be challenging. Music teachers face the challenge of working with all individuals in a student population and often engage with children who represent home environments whose native language is not English. As ELL students adjust to the new school environment, adults and peers can provide support in learning the new language. Tabors and Snow identify four periods of language use by ELL students: use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…• Near-native level of speech nonverbal behaviors coupled with use of developmentally appropriate instructional strategies." 16 English language learners may face barriers in fully accessing the music curriculum in elementary and secondary settings. For example, ELs may be "pulled out" for language instruction during music class time.…”
Section: • Few Grammatical Errorsmentioning
confidence: 99%
“…• Near-native level of speech nonverbal behaviors coupled with use of developmentally appropriate instructional strategies." 16 English language learners may face barriers in fully accessing the music curriculum in elementary and secondary settings. For example, ELs may be "pulled out" for language instruction during music class time.…”
Section: • Few Grammatical Errorsmentioning
confidence: 99%
“…The formal schooling of oral language begins in the kindergarten year, which has a significant and long-term effect on children's current and future academic success [25][26][27] because, during that year, children learn and develop memory, basic math, and literacy skills, and build fundamental science knowledge [26]. A growing body of research has been conducted to investigate issues related to kindergarten ELs' oral language proficiency, such as language interaction and oral language development [28,29], the impact of school or home factor on oral English proficiency [9,30]), and the connection between Els' first and second oral language development [31]. These studies have suggested that ELs' oral English proficiency at an early age has a critical impact on their subsequent academic performance, which further underscores the need for effective oral language instruction to better prepare ELs.…”
Section: Kindergarten Els' Oral Language Developmentmentioning
confidence: 99%